Genealogy as a Method to Legitimise Rulership in Some Balkan and Scandinavian Sources - Stankova, Vesela (Studia Ceranea, 2020)
This paper will focus on several sources from Scandinavia and the Balkans, and compare the types of genealogies portrayed in them – descent from gods, descent from another kind of supernatural being, descent from a legendary hero. The paper will examine the types of genealogies and the purpose they serve; how and why they were commissioned? Is there a difference in the establishment of the image of the ruler if the latter has descended from gods, legendary heroes, or a specific clan or dynasty? Does Christianity change the tradition of writing genealogies and the stories they retell? Are personal qualities enough to provide legitimate claims?